Critical Gaps in Shoreline Plastics Pollution Research - Melvin, Jessica; Bury, Madeline; Ammendolia, Justine; Mather, Charles; Liboiron, Max (Frontiers in Marine Science, 2021)
Shoreline surveys are an accessible and common method for monitoring plastic pollution in aquatic environments. Their results are critical to well-informed pollution mitigation efforts. Here, we show that three environmental variables: (1) coarse sediment, (2) accumulations of organic material, and (3) snow and ice are dramatically underrepresented by existing shoreline plastic pollution research efforts. We reviewed 361 published shoreline surveys, encompassing 3,284 sample sites, and found that only 4% of sites included coarse sediment, only one study described sampling organic material for plastic, and only 2.5% of sites are sampled in the presence of ice or snow. The relative absence of these environmental variables may stem from the tailoring of shoreline survey guidelines to a narrow range of shoreline environments. These three features influence plastic deposition and retention on shorelines, and their underrepresentation signals a need to recalibrate research efforts towards better methodological reporting, and regional representation and relevance.